JR-AB2-011 induces fast metabolic changes independent of mTOR complex 2 inhibition in human leukemia cells - Kořánová, Tereza; Dvořáček, Lukáš; Grebeňová, Dana; Kuželová, Kateřina (Pharmacological reports, 2024)
BACKGROUND: The mechanistic target of rapamycin (mTOR) is a crucial regulator of cell metabolic activity. It forms part of several distinct protein complexes, particularly mTORC1 and mTORC2. The lack of specific inhibitors still hampers the attribution of mTOR functions to these complexes. JR-AB2-011 has been reported as a specific mTORC2 inhibitor preventing mTOR binding to RICTOR, a unique component of mTORC2. We aimed to describe the effects of JR-AB2-011 in leukemia/lymphoma cells, where the mTOR pathway is often aberrantly activated. METHODS: The impact of JR-AB2-011 on leukemia/lymphoma cell metabolism was analyzed using the Seahorse platform. AKT phosphorylation at Ser473 was used as a marker of mTORC2 activity. mTOR binding to RICTOR was assessed by co-immunoprecipitation. RICTOR-null cells were derived from the Karpas-299 cell line using CRISPR/Cas9 gene editing. RESULTS: In leukemia/lymphoma cell lines, JR-AB2-011 induced a rapid drop in the cell respiration rate, which was variably compensated by an increased glycolytic rate. In contrast, an increase in the respiration rate due to JR-AB2-011 treatment was observed in primary leukemia cells. Unexpectedly, JR-AB2-011 did not affect AKT Ser473 phosphorylation. In addition, mTOR did not dissociate from RICTOR in cells treated with JR-AB2-011 under the experimental conditions used in this study. The effect of JR-AB2-011 on cell respiration was retained in RICTOR-null cells. CONCLUSION: JR-AB2-011 affects leukemia/lymphoma cell metabolism via a mechanism independent of mTORC2.
Keywords: nádorové buněčné linie; Mechanistic Target of Rapamycin Complex 2; Proto-Oncogene Proteins c-akt; Phosphorylation; Acute myeloid leukemia; protein RICTOR; Mitochondrial respiration; Cell Line, Tumor; AML; mTOR inhibitory; protoonkogenní proteiny c-akt; Humans; mTORC2; OCR; Rapamycin-Insensitive Companion of mTOR Protein; fosforylace; MTOR Inhibitors; leukemie; lidé; Leukemia